The foundations of mind origins of conceptual thought - Mandler, Jean Matter; Oxford scholarship online (Online service). (Oxford Oxford University Press, 2004)
This title offers a theory of how human conceptual life begins and shows how perceptual information becomes transformed into concepts.
Includes bibliographical references and index.
Keywords: Cognition in infants; Concepts in infants; Electronic books